Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14419/ijh.v4i2.6214
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of demand for subsequent doses of pneumococcal and rotavirus vaccines for children less than five years of age in Ghana

Abstract: The mortality of children which has pneumonia and diarrhoea as some of its major causes remains a major concern for all countries of which Ghana is no exception. Ghana's current child mortality rate is far above the sustainable development goal 3.2. However, given that vaccination is one of the most effective ways of preventing childhood diseases, it was surprising that, the 2014 Ghana demographic and health survey (GDHS) report showed a falling up-take or coverage in the successive doses of the pneumococcal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
4
7
0
Order By: Relevance
“…Similar findings were revealed by Immurana and Urma [10] and Immurana and Urma [11] who found employed mothers to be more probable to demand for both the Pneumococcal and Rotavirus vaccines and both the Measles and Yellow fever vaccines for children in Ghana respectively. This is because employed mothers are better empowered to afford indirect costs of vaccine utilisation such as transportation cost and therefore would be more probable to utilise it for their children relative to unemployed mothers.…”
Section: Regression Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Similar findings were revealed by Immurana and Urma [10] and Immurana and Urma [11] who found employed mothers to be more probable to demand for both the Pneumococcal and Rotavirus vaccines and both the Measles and Yellow fever vaccines for children in Ghana respectively. This is because employed mothers are better empowered to afford indirect costs of vaccine utilisation such as transportation cost and therefore would be more probable to utilise it for their children relative to unemployed mothers.…”
Section: Regression Resultssupporting
confidence: 83%
“…The result on the Brong Ahafo region is similar to the findings of Immurana and Urma [10] with regard to demand for Pneumococcal vaccine for children in Ghana. Also similar result in the case of the Eastern region was found by Immurana and Urma [11] on the less likelihood of children in the Western region of Ghana to have been given both the Yellow fever and Measles 1 vaccine.…”
Section: Regression Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover the recorded cases of yellow fever were more amongst children under-5 years (23.4%), residents in Izzi LGA (49.6%), rural residents (97.8%), and males (54.0%). The finding is consistent with previous studies (Immurana & Urma, 2016a, 2016bWamala et al, 2012), which indicated that the case number of YF was higher in under-5 children, males, and rural regions. The recorded high cases of YF among under-5 children are probably because this age category is characterised by a weak immunity to infectious diseases and a lack of naturally acquired immunity to YF.…”
Section: Nevertheless the Finding Is In Line With The World Healthsupporting
confidence: 93%
“…On the empirical front specifically on Ghana, Matthews and Diamond (1997), Bosu et al (1997), Dwumoh et al (2014), DuahOwusu (n.d.), McGlynn (2012) and Immurana and Urma (2016) have investigated factors that influence immunization utilisation among children in Ghana. However aside Immurana and Urma (2016) who investigated demand for pneumococcal and rotavirus vaccines for children in Ghana, none of these studies investigated the factors that influence the up-take of specific individual vaccines among children in Ghana.…”
Section: Introductionmentioning
confidence: 99%